The Stoic and Epicurean philosophers the complete extant writings of Epicurus, Epictetus, Lucretius [and] Marcus Aurelius. - Oates, Whitney Jennings 1904- (Random House, 1940)
From the Dust Jacket: In the writings of Epicurus, Epictetus, Lucretius and Marcus Aurelius, Greek and Roman philosophy comes into its fullest flowering. The advocates of the principles of virtue and pleasure are brought together into a single inexpensive volume for the first time; hitherto their works were obtainable only in separate, expensive editions. The four thinkers here represented have been brilliantly translated by Cyril Bailey, H. A. J. Munro, P. E. Matheson and George Long. In addition, Cleanthes' famous poem Hymn to Zeus and Matthew Arnold's Essay on Marcus Aurelius are included.